(untitled) - Clayton, Gary E. (Boston, 2001)
This brief and inexpensive paperback examines 35+ economic statistics such as GDP, inflation, unemployment, interest rates, consumer confidence, etc., from public and private sources such as the Bureaus of Economic Analysis, Labor Statistics, Census, and The Conference Board. It assumes no prior knowledge of economics and is fully updated
Keywords: Economics; Statistical methods